2022
DOI: 10.3389/fspas.2022.886140
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences in Carbon-14 Data of the 993 CE Cosmic Ray Event

Abstract: Cosmogenic nuclides such as 14C from tree rings and 10Be and 36Cl from ice cores are excellent proxies for the past extremely large solar energetic particle (SEP) events, which are dozens of times larger than the largest SEP event in the history of observation. So far, several rapid 14C increases have been discovered, which are considered to have originated from extreme SEP events (or set of successive SEP events) from verifications using multiple cosmogenic nuclide analyses in natural archives. Although these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…A similar late rise is found in Japanese cedar for the 993 CE event by Miyake et al [114], who interpret this as being affected by global atmospheric circulation patterns in different latitudinal Radiocarbon Zones, and an oceanic versus continental distinction. By contrast, in the ensemble of tree rings over 774 CE, prolonged and sharp rises are seen across these categories: there are trees showing both phenomenologies from Zones 0-2, continental or oceanic regions, different growth speeds and altitudes.…”
Section: (A) Timing Of 774 Ce Eventsupporting
confidence: 74%
See 2 more Smart Citations
“…A similar late rise is found in Japanese cedar for the 993 CE event by Miyake et al [114], who interpret this as being affected by global atmospheric circulation patterns in different latitudinal Radiocarbon Zones, and an oceanic versus continental distinction. By contrast, in the ensemble of tree rings over 774 CE, prolonged and sharp rises are seen across these categories: there are trees showing both phenomenologies from Zones 0-2, continental or oceanic regions, different growth speeds and altitudes.…”
Section: (A) Timing Of 774 Ce Eventsupporting
confidence: 74%
“…We exclude the Japanese cedar from Miyake et al. [114], as it shows a delayed rise compared to the other 993 CE datasets, and for the purposes of the present work, we await a consensus on how to interpret this.…”
Section: Methods: the Ticktack Carbon Box Model Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Such observations cannot be understood assuming that atmospheric 14 C transport occurs solely through mid‐latitudes, unless production occurred near ground levels at high latitudes. In fact, considering the 993 CE event, it is puzzling why there is no increase at all in the mean values of the low latitude zone (NH2) for the year 993 CE, as opposed to the more northern locations of NH1 and particularly of NH0 (Figure 4d of Miyake et al., 2022). All the above indicate fast high‐latitude transport of stratospheric air to troposphere consistent with Liang et al.…”
Section: Discussionmentioning
confidence: 99%
“…A fast rise of 14 C level in high-latitude trees in Finnish Lapland (Uusitalo et al, 2018) and Yamal (Jull et al, 2014) has been observed in 774 CE. Furthermore, an early elevated signal in high-latitude trees has been observed in 993 CE (Miyake et al, 2022). Such observations cannot be understood assuming that atmospheric 14 C transport occurs solely through mid-latitudes, unless production occurred near ground levels at high latitudes.…”
Section: 1029/2023gl106632mentioning
confidence: 99%